Climate voting in the US Congress: the power of public concern. Issue 2 (3rd March 2016) - Vandeweerdt, Clara; Kerremans, Bart; Cohn, Avery
Abstract: In the United States, few constituents know and understand climate policy, prioritize it as a political topic, or let their voting decisions depend on it. In these conditions, representatives would not be expected to pay heed to constituents' climate concern in their voting decisions. Still, even after controlling for the presence of interest groups, campaign finance, and legislators' party affiliation and ideology, there is a consistent link between public opinion and votes on cap-and-trade legislation in the House (and to a lesser degree in the Senate). The same is true when public opinion is simulated based on pre-vote district characteristics. Explanations for these findings are discussed.